Frozen fungi: cryogenic storage is an effective method to store Fusarium cultures for the long‐term. (12th July 2018) - Webb, K.M.; Holman, G.; Duke, S.; Greene, S.; McCluskey, K.
Abstract: Microbial culture collections provide a vast amount of genotypic and phenotypic information which are invaluable resources for future advancements in research. For most microbial strains, cryopreservation in the vapour phase above liquid nitrogen provides the most stable and long‐term storage method. However, in the case of fungal microbes, not all are suited for cryogenic storage and few studies have addressed the effectiveness of storage in the vapour phase above liquid nitrogen on a diverse collection of Fusarium species. In this work, a collection of 374 Fusarium strains from the Fungal Genetics Stock Center, including 24 unique species, were duplicated and sent to the National Laboratory for Genetic Resource Preservation for storage in the vapour phase above liquid nitrogen. After 5 years of storage the entire collection was tested for viability and phenotypic stability by using plating, cellular staining assays, assessing the number of viable cells and measuring the rate of growth of each isolate. Additionally, the rate of growth for ∼10% of the isolates were compared with the same isolates which had been stored at −80°C at the Fungal Genetics Stock Center over the same timeframe to determine if cryopreservation in liquid nitrogen vapour provided a comparable method of storage. All National Laboratory for Genetic Resources Preservation isolates grew after being stored at −165°C for 5 years. In general, the isolates that were stored at −165°C grew at a faster rate than the isolates stored at −80°C for the same period. Of the isolates stored at −165°C, most had greater than 80% cell viability, however, those isolates that had less than 50% cell viability generally also had fewer conidia germinate. These isolates may be at a greater risk for storage over longer times. In conclusion, storage at −165°C liquid nitrogen provided reliable preservation of a diverse collection of Fusarium spp. over 5 years, and culture viability data indicates that they will remain viable during additional storage for longer periods. Abstract : Microbial culture collections provide a vast amount of genotypic and phenotypic data for future research. While cryopreservation in the vapor phase above liquid nitrogen (−165°C) provides the most stable and long‐term storage method, few studies have addressed the effectiveness of cryopreservation on a diverse collection of fungi. Fusarium species cryogenically stored at −165°C (CO) grew at a faster rate than the same isolates which had been stored at −80°C (KS) after 5 years. Likewise, most isolates stored cryogenically had greater than 80% cell viability, suggesting that they will remain viable during additional storage for longer periods.